Thinking as a Student: Stimulating Peer Education in the Humanities with an Undergraduate Teaching Assistant - Lara Karpenko; Steven Schauz (Journal of the Scholarship of Teaching and Learning, 2017)
In this article, I argue that peer educational experiences should be incorporated into the undergraduate humanities classroom by providing a case study of a successful Undergraduate Teaching Assistant (UTA) pilot. In keeping with Topping & Ehly’s (2001) criteria for successful peer education, I assigned the UTA a significant role in direct instruction. Partly owing to the UTA’s active classroom role, the experience enhanced learning for students and helped me create a dynamic, critically-engaged class environment. The experience also provided an opportunity for the UTA to engage in deep learning and develop a professional identity; near the end of this article, the UTA shares his reflection about the experience.